(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2026)
The history of dentistry reflects the development of dental care from ancient practices to modern scientific approaches. Over millennia, dentistry has evolved through cultural, medical, and technological advancements. Ancient civilizations, including the Egyptians, Greeks, and Romans, practiced basic dental procedures, such as tooth extraction and remedies for oral diseases.